Hakikat, Makna Konsep Tentang Filsafat Manajemen Pendidikan Islam: Pendekatan Systematic Literature Review - Nizar, Muhammad Alang Khairun (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2024)
The ultimate goal of Islamic education lies in the realization of complete submission to Allah at the individual, community and human levels. This is the direction of all management activities of educational institutions in order to achieve Islamic goals. This article aims to explain the nature and philosophy of educational management from an Islamic perspective. The method used in this article is qualitative research with a Systematic Literature Review approach. Article articles were collected from Google Scholar via the PRISMA (Preferred Reporting Item for Systematic Reviews and Meta-analyses) process. Then descriptive content analysis was carried out. The results found that the essence and philosophy of educational management in an Islamic perspective originates from the Al-Qur'an and hadith where in an Islamic perspective, Management in an Islamic perspective implements the principles of Islamic teachings which are in line with the concept of management, namely deliberation (shura), mandate (amanah), and justice (al-'adl) and educational management science must contain Islamic principles and values ​​that can guide students towards their own existence.